The use of psychodrama in the treatment of group psychotherapy of alcohol and substance dependents - Coşkun, Beyhan; Çakmak, Duran (Journal of Dependence, 2005)
Objective: This study was done for assessing psychodrama’s effectiveness on group psychotherapy of alcohol /drug addicts in AMATEM Bakırköy State Hospital for Mental & Neurological Diseases.Method: Psychodrama tecniques were used in group psychotherapy. Patients were assessed with SCS (Social Comparison Scale); SAS (Submissive Acts Scale); STAEI (State-Trait Anger Expression Inventory; TAS (Toronto Alexithymia Scale) at the beginning and end of the 28 days therapy program. These scales were chosen because of those parameters had been related with relapse and also were problematical emotional, behavior areas in addicts.Results: SAS scale’s scores differences at the beginning and end of the therapy were statistically significant. SCS’s & STAEI’s anger toward one’s self subscale’s differences were nearly statistically significant. In TAS scale the number of people diagnosed as alexithymic were reduced and also before and after tests mean scores were also diminished. In group therapy of alcohol/drug addicts using psychodrama techniques in traditional verbal method; psychotherapy’s power had been increased and also accelerated.Conclusion: Our hypothesis was by using this method; subject’s inability to cope with their fears would be lessened; some submissive behaviours acting in social situations would be changed; perceptional self schemas would be changed in positive way end also anger degree and expression of it would been changed positively. Our results were supported this hypothesis in our study.
Keywords: Alcohol/substance use; addiction; psychodrama; group psychotherapy